Productive Performance and Blood Biochemical Parameters of Dairy Cows Fed Different Levels of High-Protein Concentrate - Buryakov, Nikolai; Aleshin, Dmitrii; Buryakova, Maria; Zaikina, Anastasya; Nasr, Mohammed; Nassan, Mohamed; Fathala, Mohamed (Frontiers in Veterinary Science, 2022)
Ayrshire is considered one of the major dairy breeds. The current study was investigated the productive traits and some blood biochemical parameters of high yielding Ayrshire dairy cows fed different levels of "Agro-Matic" protein concentrate. 45 high yielding Ayrshire cows were selected and divided to into 3 groups (each 15). The 1st control group fed the basal ration, while, the 2nd and 3rd groups fed basal ration with replacing sunflower cake by different levels of "Agro-Matic" (1 and 1,5 kg/head/day), respectively.‎ Balancing experiment, milk and blood samples were collected. The ratio of rumen undegradable protein to rumen degradable protein during the period of lactation was higher in the experimental groups than control group and represented (55.04, 62.14 and 41.73 %), respectively. Supplementing of 1kg/head/day of "Agro-Matic" had a beneficial effect on the digestibility of crude protein. There was 3kg/day increase of daily milk yield of 4% fat corrected milk with "Agro-Matic" supplementation when compared with the control cows with an increase of the total milk yield of 4% fat throughout the entire lactation season in group 2 (351.9kg) and group 3 (987kg) when compared with the control group. Blood total protein was higher in the 2nd experimental group (86.9 vs. 77.8g/l) than that of the control with a decrease in urea concentration. Consequently, the inclusions of "Agro-Matic" protein concentrate has a positive impact on increasing milk production and optimize rations in terms of the amount of non-digestible protein and economic efficiency of milk production.